AN ANALYSIS OF FIGURATIVE LANGUAGE ON CINDERELLA, RUMPELSTILTSKIN, THE FISHERMAN AND HIS WIFE AND THE SLEEPING BEAUTY THE WOODS BY CHARLES PERRAULT AND THE BROTHERS GRIMM - Afrina, Poppy; Setiarini, Ni Luh Putu; Anita, Anita (Journal of Language and Literature, 2016)
Figurative language exists to depict a beauty of words and give a vivid description of implicit messages. It is used in many literary works since a long time ago, including in children literature. The aims of the research are to describe about kinds of figurative language often used in Cinderella, Rumpeltstiltskin, The Fisherman and His Wife and The Sleeping Beauty in the Woods By Charles Perrault and the Brothers Grimm and also give a description the conceptual meaning of figurative language used in Cinderella, Rumpeltstiltskin, The Fisherman and His Wife and The Sleeping Beauty in the Woods By Charles Perrault and the Brothers Grimm. The writer uses a descriptive qualitative method in this research.Keywords: Analysis, Figurative Language, Children.